[Aerial View of Cal Poly] - News Bureau, California State Polytechnic University, San Luis Obispo::::::::: (1964)
View of main campus, Aeronautical Hangar, Agricultural Engineering, red-brick dorms, North Mountain, Science, Engineering East, Engineering West, English, Dexter, Poly Ninos (Vetville), Administration, Mott Gym, Poly Canyon - looking south